TARI RENTAK BULIAN SEBAGAI EKSPRESI BUDAYA DAN REFLEKSI KEINDAHAN MASYARAKAT INDRAGIRI HULU PROPINSI RIAU - Erlinda Erlinda; Asmaryetti Asmaryetti; Syaiful Erman (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
Studies on the dance Rentak Bulian in Riau Community are kinds of discussions aboutfield empirical reality with the problems of dance as a cultural expression among its community. In addition to describing the existence of the dance, this study also analyses the reflection of its beauty by investigating its aspects of movement, musics, costumes, properties, supports, and presentation. Analysis is done descriptively, qualitative, and interpretatively. The dance of Rentak Bulian constitutes a cultural expression of the Malay community of Petalanganan Talang Mamak, Indragiri Hulu, Rengat. Although the ritual of Bulian has transformed into a performance arts, seeing from either its form, function, and meaning, the ritual's magic component must still be staged in order to fulfil its performance demand. Among the rituals are: there must be seven virgin female dancers; the dancers are in their clean period (not in menstruation), there must be a strong male dancer, the dancers are not related in blood, all dancers must acquire consents from the village elders, they must be blessed with sandalwood smoke, musical instruments must be casted, the young bunch of areka nut must be selected, and the fireplace must not be casted any spell.